PENENTUAN LOKASI PENEMPATAN TCSC PADA SISTEM KELISITRIKAN SULAWESI SELATAN DAN BARAT MENGGUNAKAN INDEKS SENSITIVITAS - Nur Vidya Ramadhani; Rini Nur Hasanah; Hadi Suyono (Universitas Nusa Cendana, 2022)
The transmission line that functions to distribute energy from the generating center to the load center must function efficiently. However, the extensive network allows the line operation to be inefficient. This allows the occurrence of power losses and voltage drop in the system. Therefore, efforts are needed to effectively utilize the available power system capacity, one of which is by installing new devices such as TCSC (Thyristor Controlled Series Capacitor). The method used is the Sensitivity Index. Power flow analysis using PSAT (Power System Analysis Toolbox) program. Based on the data analysis that has been done, it was found that the most sensitive line is Pngkep70kV–Mndai. After the installation of the TCSC device on the sensitive line, there was a decrease in power losses and an increase in voltage stability in the system compared to before the installation of TCSC. Thus it can be concluded that the installation of TCSC provides a positive performance on the electricity system of South and West Sulawesi.